Towards a Critical Cognitive Linguistics? - Stockwell, Peter; Mhammed, Elmellakh (LANGUAGE ART, 2019)
This paper asks whether the Cognitive Linguistics and Critical Discourse Analysis share any common basics and investigate a possible synthesis between them. The Critical Discourse Analysis can make the cognitive framework self-reflexive and more oriented towards the social context, reinforcing a contextualized analysis of meaning. The Cognitive Linguistics models can offer tools to Critical Discourse Analysis for theorizing analytical concepts like metaphorical representations and context. Furthermore, a synthesis will be a possible option if the two disciplines share a common domain. The accommodation must be made at the level of theoretical inconsistencies.